MATERNAL FOOD RESTRICTION DURING LACTATION PROMOTES RENAL DYSFUNCTION IN THE MALE OFFSPRING AT ADULTHOOD - Maria Eduarda R. da Silva; Keilah V. N. Cavalcante; Marcos Divino Ferreira-Junior; Ariel Penha Carvalho da Mota; Isadora Silva Rosa; Jose Antonio Barbosa Lima Sobrinho; Rodrigo Mello Gomes (Arquivos do Mudi, 2023)
The aim of this work is to evaluate the renal function and the morphology of the kidneys inthe offspring, of both sexes, of mothers who underwent a 50% food restriction duringlactation. Pregnant Wistar rats were divided into two experimental groups: Control group(CO) fed with standard diet and Food restriction (FR) fed with standard diet restricted to 50%of the daily food intake of CO mothers. The intervention was carried out from the 1st to the14th day of lactation, after from the 14th to the 21st day of lactation. The offspring of bothgroups were fed with standard diet and water ad libitum until 120-day-old. At the end of theexperimental period 24-hour urine collection was performed. After euthanasia biochemicaland histological analysis were performed. Male and female FR offspring showed no change inbody weight or kidney weight compared to control counterparts. Male FR showed a reductionin the glomerular filtration rate (CO 3.22±0.35 vs FR 2.25±0.12; ml/min) and increased totalurinary protein (CO 82.82±11.79 vs FR 123.8±8.37; mg/dL) compared to the CO offspring.We observed a reduction in glomerular area in the male FR (CO 7259±271.7 vs FR6349±106.3; μm 2 ) in comparison to CO offspring. In conclusion, maternal food restrictioncauses functional and morphological kidney damage in adult males, being a sex-specificresponse since females did not show alterations.